Solvability for a Coupled System of Fractional $p$-Laplacian Differential Equations at Resonance (Communications in Mathematical Research, 2020)
In this paper, by using the coincidence degree theory, the existence of solutions for a coupled system of fractional $p$-Laplacian differential equations at resonance is studied. The result obtained in this paper extends some known results. An example is given to illustrate our result.
Keywords: $p$-Laplacian; coincidence degree; existence; fractional differential equation; boundary value problem